Perancangan Aplikasi Duplicate Video Scanner Menerapkan Algoritma Sha-256 - Rewindo Siregar (Graha Mitra Edukasi, 2022)
In this increasingly advanced era, new technologies that have never been imagined before are increasingly emerging, starting from the emergence of computers, cellphones, and many more. One of the emerging technologies is MPEG4 (Moving Picture Expert Group)-4 Video Player 3 or better known as MP4. MP4 Player can make a person listen to video digitally, no need to use cassettes or CDs like in the past and allows millions of people around the world to exchange music recordings through computers connected to computer networks. MP4 format which is commonly played by MP4 Player is one of the most frequently used video formats in video data storage. In cryptography there is a hash function which is a one-way encryption that produces a value that has a fixed length of a message. In this case the intended message is a video file. The hash function can be used to generate the identity of a video file, where if there are two or more video files that have the same hash value, it can be concluded that the video file is duplicate or duplicate. This will certainly make it easier for users to delete duplicate or duplicate video files.